Determinants of Successful Acquisition: A case of Hummer - MO, LI (2009)
In 2009, the public pay close attention to the bankruptcy of General Motors Corporation. and the acquisition of Hummer brand by Sichuan Tengzhong Heavy Industrial Machinery Co. Ltd.. This paper analyzes the motivations behind the overseas acquisition from the perspectives of both GM and Tengzhong and discusses the advantages and disadvantages of Tengzhong. Although the prospects of the Hummer deal are not as good as expected, this paper further attempts to explore what we can learn from the previous analysis of the disadvantages of Tengzhong and what possible measures could be taken for future improvement.